Dampak Penggunaan LKS Berbasis PBL terhadap Kemampuan Berpikir Kritis Siswa Kelas XI MIA di SMA Negeri 2 Jeneponto - M. Natsir; Edi Hasan; Muhammad Wajdi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to investigate the effect of implementing Student Worksheets (LKS) based on the Problem Based Learning (PBL) model on students' critical thinking skills on the circulatory system material in class XI MIA SMA Negeri 2 Jeneponto. The approach used is experimental with a quasi-experimental design of a non-equivalent control group type. The research sample consisted of two classes, namely the experimental class using PBL with LKS (XI MIPA 1) and the control class using the conventional learning model (IPA 3). The sample selection was carried out using the purposive sampling method. This study involved two variables, namely the independent variable in the form of PBL-based LKS and the dependent variable in the form of students' critical thinking skills. The research process consists of three main stages: preparation, implementation, and data analysis. In the preparation stage, the development of research instruments was carried out, such as lesson plans (RPP), LKS, and pre-test and post-test questions. The implementation stage involved giving a pre-test, learning treatment using PBL with LKS in the experimental class, and a post-test to measure the improvement of critical thinking skills. Data analysis was conducted using descriptive and inferential analysis, including independent sample t-test. The results of the hypothesis test showed a Sig (2-tailed) value of 0.000, which is smaller than 0.05, so the null hypothesis H0 is rejected and the alternative hypothesis H1 is accepted. This shows that the implementation of PBL-based LKS has a positive and significant effect on students' critical thinking skills. Thus, the PBL model through LKS has proven effective in improving students' critical thinking skills on the circulatory system material.